Cold stimuli, hot topic: An updated review on the biological activity of menthol in relation to inflammation - Cheng, Haojin; An, Xuemei (Frontiers in Immunology, 2022)
Background: Rising incidence of inflammation-related diseases is an increasing concern nowadays. However, while menthol is a wildly-used and efficacious complementary medicine, its pharmacological mechanism still remains uncertain. Superimposed upon that, the aim of this review is to summarize the contemporary evidence of menthol’s anti-inflammatory activity. Methods: Using the pharmacopoeias and electronic databases, including Web of Science, PubMed and CNKI, this study analysed the relevant research articles and review articles from 2002 to 2022 and concluded those results and conjectures to finish this article. Results: The decrease in pro-inflammatory cytokines and related inflammatory markers, as well as associated pathway activation, was found to play the greatest role in the protective effects of menthol against inflammatory damage or association with protection against chronic inflammation. Conclusion: This review mainly concludes the progress in menthol’s anti-inflammatory activity. Further studies are needed to establish relationships of the mechanisms of action, and to clarify the clinical relevance of any anti-inflammatory effects.